Noise induced hearing loss among drivers of compressed natural gas (CNG) run three-wheeler auto rickshaws in Dhaka Metropolitan City, Bangladesh: Noise induced hearing loss among drivers of CNG run three-wheeler auto rickshaws - Rahman, Mohammad Mostafizur; Begum, Dilruba; Rahman, Abul Fazal Shah Muhammad Shazedur; Chakrabarty, Swarnali; Khanom, Sayeda; Rahman Orpa, Tashfin (Journal of the Medical College for Women & Hospital, 2025)
Background: Noise is an occupational hazard that affects worker health and safety. Prolonged exposure to noisy environment results in hearing loss of the affected individuals. Compressed Natural Gas (CNG) run three-wheeler auto rickshaw drivers in Dhaka Metropolitan City are frequently exposed to heavy traffic and are prone to develop more vulnerable They have to work in excessive sound levels and this repeated exposure to noise on daily basis could result in noise induced hearing loss (NIHL). However, the hearing status in CNG run three-wheeler auto rickshaw drivers is unknown as they are not addressed in previous studies. Aim: The aim of the study was to assess the hearing threshold status of the auto rickshaw drivers of Compressed Natural Gas (CNG) run three-wheeler in Dhaka Metropolitan City of Bangladesh and comparing it with the control group. Materials and Method: The study was a cross sectional study and conducted in the Department of Physiology, Dhaka Medical College, Dhaka, from January 2020 to December 2020. After fulfilling the ethical aspect, a total number of 305 drivers of CNG run 4-stroke three-wheeler auto rickshaws were selected purposively from different vehicles stands of Dhaka Metropolitan City on the basis of inclusion and exclusion criteria. In addition, 100 apparently healthy office workers were taken as control group for A comparison. Informed written consent was taken from all the participants. Pure tone air and bone conduction, parameters were tested and data was collected in pre-designed structured questionnaire form. Results: A total of 31.47% of auto rickshaw drivers suffered from NIHL (95% CI 11.8%-22.5%) Audiometric results showed moderate degree of hearing loss have higher rate (62.50%) than mild or severe degree of hearing loss. The mean hearing thresholds showed a typical dip at 4000 to 6000 Hz. Conclusion: The occupational hazards of auto rickshaw driving significantly increased the hearing threshold values. It is found that the mean hearing threshold values for autorickshaw drivers increase at higher frequencies at higher frequencies with increase in driving experience. Therefore, drivers must be educated about the hearing conservation during driving and should be periodically evaluated to detect audiological damage. J Med Coll Women Hosp.2025; 21 (2): 110-122